El mejoramiento de la calidad de vida de los trabajadores en la cultura organizacional de la Empresa Pública Metropolitana de Agua Potable y Saneamiento de Quito en el 2017 - García Veloz, Carmen Lorena (2020)
The purpose of this research is to establish mechanisms and strategies that seek to improve or increase the levels of quality of life and satisfaction of the servers of the company Empresa Pública Metropolitana de Agua Potable y Saneamiento - EPMAPS Agua de Quito; In this way, it is possible to establish an optimal scenario for personal development, work autonomy, support and identification, and fulfillment of objectives, within the company. To achieve the objective, the levels of quality of life presented by the servers were identified, and their correlation on the organizational culture, measuring and identifying the dimensions with irregularities and problems in order to seek the improvement, impact, characteristics and positive influence for the company.